RELATIONSHIP BETWEEN NUMBER AND REGION OF TOOTH LOSS WITH THE QUALITY OF LIFE IN THE ELDERLY. - Fatmasari, Diyah; Satuti, Nindita Enhar; Wiyatini, Tri (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Prevalence of tooth loss due to extraction is highest in the elderly aged 65 years and over. Tooth loss means loss of tooth function therefore it affects the quality of life. It seems a reflection of a person's comfort and disability in terms of limited physical, psychological, and social functions. The aim of this study was to determine the relationship between number and region of tooth loss with the quality of life in the elderly at the Margo Mukti Elderly Social Service Home, Rembang.Method: Research design was observational study with cross sectional approach. Sample size was 58 elderly people taken from the total population of 300 elderly who live at social services home. Data was collected by examining the number and region of tooth loss followed by interviews using the Oral Health Impact Profile (OHIP-14) questionnaire. Data analysis was performed by univariate and bivariate analysis, using the test chi square and Kolmogorov Spirnov to determine the relationship between independent and dependent variables.Result: The results showed significance of statistical was found at relation number and region of tooth loss with quality of life (0.006). The highest number of tooth loss was in the range of 6-23 teeth. Anterior region was the most tooth lost. Most of elderly (67.2%) have good quality of life.Conclusion: There is relationship between number and region of tooth loss with quality of life related to oral health